ANALISIS PENGARUH SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BANYUWANGI DAN KABUPATEN BULELENG SEBAGAI KAWASAN PENGEMBANGAN PARIWISATA TERINTEGRASI - Asyifa Ridha Septiana; Niniek Imaningsih (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
Banyuwangi Regency and Buleleng Regency directly border the Bali Strait, which connects the islands of Java and Bali. As border regions included in the integrated tourism development area, both have high tourism potential and have experienced an increase in the number of tourists in recent years. However, the growth of the tourism sector has not been followed by a proportional increase in the realization of local own-source revenue (PAD). In addition, the contribution of tourism sector revenue to PAD in these two regions remains low, with an average contribution of only 0.68% of the total PAD in Banyuwangi Regency and 1.13% in Buleleng Regency. The purpose of this study is to determine the effect of the number of domestic tourists, the number of international tourists, the number of hotels, and the number of restaurants on local own-source revenue in Banyuwangi and Buleleng Regencies during the period 2009–2023. This study uses local own-source revenue (Y) as the dependent variable and the number of domestic tourists (X1), number of international tourists (X2), number of hotels (X3), and number of restaurants (X4) as the independent variables. The data used are secondary data obtained from publications by the Central Bureau of Statistics (BPS) of Banyuwangi Regency, Buleleng Regency, East Java Province, and Bali Province, as well as the official websites of the Tourism Offices of East Java and Bali Provinces. The study employs multiple linear regression analysis using SPSS version 26. The results of the study indicate that the number of domestic tourists has no significant effect on PAD in Banyuwangi Regency but has a significant effect in Buleleng Regency. The number of international tourists does not have a significant effect on PAD in either Banyuwangi or Buleleng. The number of hotels has a significant effect on PAD in both regencies. The number of restaurants significantly affects PAD in Banyuwangi Regency but not in Buleleng Regency.